The SAGE handbook of conflict communication - Oetzel, John G; Ting-Toomey, Stella (Sage Publications, 2013)
"This second edition of the award-winning The SAGE Handbook of Conflict Communication emphasizes constructive conflict management from a communication perspective, identifying the message as the focus of conflict research and practice. Editors John G. Oetzel and Stella Ting-Toomey, along with expert researchers in the discipline, have assembled in one resource the knowledge base of the field of conflict communication; identified the best theories, ideas, and practices of conflict communication; and provided the opportunity for scholars and practitioners to link theoretical frameworks and application tools. Fully updated with the latest research throughout, the second edition offers new chapters on qualitative and quantitative research methods for conflict, intimate partner violence, family dynamics, mental health, negotiation, workplace bullying, healthcare conflict, identity and intercultural conflict, the middle way approach, conflict in the global workplace, the culture-based situational conflict model, community ethics and engagement, spirituality and conflict, and trust in academic-community partnerships."--Publisher's website.